Endometriosis-associated pain and new therapeutic options: A review - Maria I. Yarmolinskaya; Alexandra K. Beganova; Anastasia S. Revenko (IP Berlin A.V., 2023)
Pelvic pain is one of the most common and significant clinical symptoms of endometriosis. The complex pathogenesis and paradoxical nature of endometriosis-associated pain, its chronicity and centralization, a marked decrease in the quality of life of patients, the lack of an "ideal" and effective remedy with no limitation for all patients, as well as the progressive and recurrent nature of the disease are factors that determine the need for novel, additional therapeutic options. The pain mechanisms in endometriosis and the potential pathogenetic effects of trans-resveratrol and indole-3-carbinol on various aspects of endometriosis-associated pain are addressed based on the literature sources presented in electronic databases PubMed, CyberLeninka, and Google Scholar. The described pharmacological properties of the compounds suggest that the combined use of trans-resveratrol and indole-3-carbinol is a pathogenetically justified and promising treatment for complex endometriosis-associated pain.